The Effect of Mn3+ Substitution on the Electric Field Gradient in a HoFe1−xMnxO3 (x = 0–0.7) System - Yuriy V. Knyazev; Maksim S. Pavlovskii; Timofei D. Balaev; Sergey V. Semenov; Stanislav A. Skorobogatov; Aleksey E. Sokolov; Denis M. Gokhfeld; Kirill A. Shaykhutdinov (Crystals)
The effect of the Mn3+ ion on the local distortions of FeO6 octahedra in orthoferrite samples was investigated. Mössbauer spectroscopy measurements for a series of <semantics>HoFe1−xMnxO3</semantics> (x = 0–0.7) orthoferrite samples with the space group Pnma were carried out at temperatures above the Néel point (700 K). The electric field gradient (EFG) tensor on Fe ions for these compounds was found using first-principle calculations. The concentration dependence of quadrupole splitting was obtained using experimental and theoretical data. Mn3+ cations were found to affect the Mössbauer spectra mainly due to distortions of the crystal lattice. Theoretical calculations show that the values of all electric field gradient components increase significantly with the manganese concentration in the system, and the eigenvectors <semantics>exx</semantics> and <semantics>eyy</semantics> of the electric field gradient tensor sharply change their direction at concentrations of x > 0.1.